Clinical Analysis of Pediatric Opsoclonus-Myoclonus Syndrome in One of the National Children's Medical Center in China - Zhu, Haixia; Wu, Wenlin; Chen, Lianfeng; Hou, Chi; Zeng, Yiru; Tian, Yang; Shen, Huiling; Gao, Yuanyuan; Zhang, Yani; Peng, Bingwei; Chen, Wen-Xiong; Li, Xiaojing (Frontiers in Neurology, 2021)
Objective: To study the clinical characteristics and treatment of pediatric opsoclonus-myoclonus syndrome (OMS). Methods: We analyzed the clinical data of nine children OMS between June 2017 and Nov 2020. Results: Nine children (M/F= 3:6, median onset age was 18 months) diagnosed with OMS were included in the study. Before onset, human rhinovirus and respiratory syncytial virus were seen in one patient, respectively. And one patient received Japanese encephalitis vaccination. Three patients had neuroblastoma, and one patient had ganglioneuroblastoma. All patients' symptoms were improved after receiving surgery (for four patients with tumor), intravenous human immunoglobulin and pulsed methylprednisolone. However, four patients without mass relapsed and became relapse free after rituximab treatment. The relapse rate was 44.4% (4/9). The OMS severity score at the last follow-up was significantly lower than the OMS severity score at onset (3.0±1.0 vs 11.0±2.2, paired-samples t test, P<0.001). All patients had at least one item of neurological symptoms or neuropsychological disturbances. Conclusion: For pediatric OMS, human rhinovirus infection and respiratory syncytial virus infection can be seen before onset. Rituximab is effective in reducing relapse. Improving recognition and long-term prognosis in OMS is urgent.